Dakwah Kepada Orang Tua Berdasarkan Kisah Nabi Ibrahim As dalam Al-Qur’an (Studi Tafsir Tematik) - Sesvia, Sesvi; Nisa, Afdilla (SURAU : Journal of Islamic Education, 2024)
Islam, as a religion that conveys a message of peace and truth to humanity, has da'wah as one of the important pillars in its spread. In Islam, family and da'wah are a series that cannot be separated. In Islamic preaching, the Prophet and Apostles have played an important role in fulfilling the mission of religion, namely preaching to humans, especially to families. This research will reveal how da'wah to parents is based on the story of the Prophet Ibrahim AS in the Koran as well as the methods and materials used for da'wah. This research is a type of qualitative research by collecting data from the literature. The main sources for this thesis are Classical Tafsir and Contemporary Tafsir. The research metho is a descriptive-analytical method, using thematic interpretation theory in interpreting Al-Qur'an verses regarding the preaching of the Prophet Ibrahim AS to parents based on Classical Tafsir and Contemporary Tafsir. The results of this research found that the preaching of Prophet Ibrahim AS to parents was contained in 7 letters, namely in Q.S. Al-An'am verses 74-79, Q.S. Maryam verses 42-48, Q.S. Anbiya verses 52-56, Q.S. Ash-Shaffat verses 85-86, Q.S. Ibrahim verse 41, Q.S. Ash-Syu'ara verse 86, and Q.S. At-Taubah verse 114. Based on the results of the interpretation of Classical and Contemporary Tafsir, the preaching of Prophet Ibrahim AS to parents was delivered politely and gently. The da'wah material used by Prophet Ibrahim AS according to interpreters of Classical Tafsir and Contemporary Tafsir is monotheism, while the method used by Prophet Ibrahim AS to preach to his parents is with Hikmah and Al-Mau'idzah al-hasanah (giving advice in good language), as well as Da'wah bil hal in preaching to his parents. AbstrakIslam sebagai agama yang menyampaikan pesan kedamaian dan kebenaran kepada umat manusia, memiliki dakwah sebagai salah satu pilar penting dalam penyebarannya. Dalam Islam, keluarga dan dakwah merupakan satu rangkaian yang tidak dapat dipisahkan. Dalm dakwah islam Nabi dan Rasul telah memainkan peran penting dalam menunaikan misi agama yaitu berdakwah kepada manusia terutama kepada keluarga. Penelitian ini akan mengungkap bagaimana dakwah kepada orang tua berdasarkan kisah Nabi Ibrahim AS dalam Al-Qur’an serta metode dan materi dakwah yang digunakan.Penelitian ini termasuk jenis penelitian kualitatif dengan mengumpulkan data secara kepustakaan. Sumber utama skripsi ini adalah Tafsir Klasik dan Tafsir Kontemporer. Metode penelitiannya adalah metode deskriptif-analitis, dengan menggunakan teori tafsir tematik dalam menafsirkan ayat Al-Qur’an terhadap dakwah Nabi Ibrahim AS kepada orang tua berdasarkan Tafsir Klasik dan Tafsir Kontemporer. Hasil penelitian ini menemukan bahwa dakwah Nabi Ibrahim AS kepada orang tua terdapat di dalam 7 surat yaitu dalam Q.S. Al-An’am ayat 74-79, Q.S. Maryam ayat 42-48, Q.S. Anbiya ayat 52-56, Q.S. Ash-Shaffat ayat 85-86, Q.S. Ibrahim ayat 41, Q.S. Asy-Syu’ara ayat 86, dan Q.S. At-Taubah ayat 114. Berdasarkan hasil penafsiran Tafsir Klasik dan Kontemporer bahwa dakwah Nabi Ibrahim AS kepada orang tua disampaikan dengan sopan dan lemah lembut. Adapun materi dakwah yang digunak Nabi Ibrahim AS menurut penafsir Tafsir Klasik dan Tafsir Kontemporer yaitu tauhid sedangkan metode yang digunakan Nabi Ibrahim AS berdakwah kepada orang tuannya yaitu dengan Hikmah dan Al-Mau’idzah al-hasanah (memberikan nasehat dengan bahasa yang baik), serta Dakwah bil hal dalam berdakwah kepada orang tuanya.